Complete guide to painting in acrylics - Kloosterboer, Lorena (Tunbridge Wells, United Kingdom Search Press Ltd, 2015)
This comprehensive and accessible reference guide provides an in-depth exploration into the art of painting with acrylics, and has been created as one book that will accompany the reader on the complete journey from beginner to artist. With expert advice and step-by-step guidance in a wide range of techniques, this is an indispensable resource for beginning artists, students, and experienced painters alike. Drawing on the expertise of master painters from around the world, Painting in acrylics covers every aspect of working in acrylics in detail, from materials and mediums to tools and techniques. It is also a very practical approach, brimming with demonstrations to explain and reinforce the essential skills, and offering useful insights into all stages of the creative process. Accompanied by a wealth of images, and with a useful reference section with technical data and notes on commissions, selling and exhibiting, this is the ultimate desktop resource for artists, students, and hobbyists alike.
Includes index.
Keywords: Acrylic painting -- Technique